2020
DOI: 10.18632/aging.102863
|View full text |Cite
|
Sign up to set email alerts
|

ATM is a key driver of NF-κB-dependent DNA-damage-induced senescence, stem cell dysfunction and aging

Abstract: NF-κB is a transcription factor activated in response to inflammatory, genotoxic and oxidative stress and important for driving senescence and aging. Ataxia-telangiectasia mutated (ATM) kinase, a core component of DNA damage response signaling, activates NF-κB in response to genotoxic and oxidative stress via posttranslational modifications. Here we demonstrate that ATM is activated in senescent cells in culture and murine tissues from Ercc1-deficient mouse models of accelerated aging, as well as naturally age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 78 publications
(104 reference statements)
0
55
0
Order By: Relevance
“…Although cGAS senses double stranded DNA (dsDNA) in a sequence-independent manner ( Li et al, 2013 ), the molecular mechanisms by which cGAS recognizes CCF are poorly understood. Recent work has suggested that the recognition of CCF by cGAS is potentiated by CCF-bound topoisomerase one cleavage complex (TOP1cc) in a dsDNA-dependent manner in HRasV12 or etoposide-induced senescent IMR90 ( Zhao et al, 2020b ). Chromatin architectural non-histone DNA-binding protein high-mobility group Box 2 (HMGB2) stabilizes the interaction between cGAS and TOP1cc ( Zhao et al, 2020a ).…”
Section: Ccf In Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cGAS senses double stranded DNA (dsDNA) in a sequence-independent manner ( Li et al, 2013 ), the molecular mechanisms by which cGAS recognizes CCF are poorly understood. Recent work has suggested that the recognition of CCF by cGAS is potentiated by CCF-bound topoisomerase one cleavage complex (TOP1cc) in a dsDNA-dependent manner in HRasV12 or etoposide-induced senescent IMR90 ( Zhao et al, 2020b ). Chromatin architectural non-histone DNA-binding protein high-mobility group Box 2 (HMGB2) stabilizes the interaction between cGAS and TOP1cc ( Zhao et al, 2020a ).…”
Section: Ccf In Signalingmentioning
confidence: 99%
“…An additional unaddressed question is whether the DDR drives SASP exclusively through CCF formation. Supporting the possibility of multiple pathways linking DDR to SASP, ATM has been shown to phosphorylate NF-κB pathway regulator NEMO in response to acute DNA damage, as well as senescence contexts, activating NF-κB ( Wu et al, 2006 ; Zhao et al, 2020b ). Lastly, it is unclear whether cytoplasmic localization of γH2AX and other chromatin-associated proteins has additional signaling roles in senescent cells beyond cGAS-STING pathway activation.…”
Section: Perspectivementioning
confidence: 99%
“…Interestingly, persistent DDR signaling mediated by ATM activation has been reported to contribute also to the acquisition of a proinflammatory senescence-associated secretory phenotype (SASP). It has been recently demonstrated in a model of naturally aged mice that activation of the ATM-NEMO-NF-κB axis is necessary for senescence induction and SASP, which in turn elicits DDR and SASP activation also in neighboring cells, thereby creating a proinflammatory environment ( Zhao et al, 2020 ). Genetic or pharmacological inhibition of ATM reduces the adverse effects of chronic DNA damage, impinging on cellular senescence, improving stem cell functionality and extending health span.…”
Section: The Autophagy-senescence Connection In the Ddr: Role Of Atm mentioning
confidence: 99%
“…This could be achieved by targeting signaling cascade upstream of the SASP of senescent disc cells, such as NF- κ B or p38 MAPK as well as related regulators [ 12 , 87 , 117 ]. For instance, depletion of ATM downregulates the expression of SASP factors like ADAMTS and MMPs and significantly attenuates age-associated IDD [ 118 , 119 ]. However, the SASP expression on different cells, tissues, and organs is not always constant considering the diversity of senescence types [ 65 ].…”
Section: The Promising Therapy For Idd: Senotherapiesmentioning
confidence: 99%